The need for Positive Adjustment Policies in the 1980s - Wolfgang Michalski (Intereconomics, 1983)
In view of the close relationship between macro-economic performance, structural adjustment and international trade, the OECD Council established in 1979 a programme of work on Positive Adjustment Policies. Under this mandate, a Special Group of the Economic Policy Committee (under the chairmanship of Dr. Hans Tietmeyer, presently Secretary of State in the Federal Ministry of Finance in Bonn) was to review the macro-economic, structural and international implications of industrial, regional, manpower and other micro-economic policies, and to examine the adjustment policies of individual member countries. This work resulted in a Ministerial Declaration in 1982 on Positive Adjustment Policies and in a Final Report of the Special Group which is to be published shortly. The following article by Prof. Wolfgang Michalski, who directed this OECD project, is a résumé of the main conclusions.
Keywords: 330